The influence of Totten Glacier on the Late Cenozoic sedimentary record. Issue 4 (August 2020) - Donda, Federica; Leitchenkov, German; Brancolini, Giuliano; Romeo, Roberto; De Santis, Laura; Escutia, Carlota; O'Brien, Philip; Armand, Leanne; Caburlotto, Andrea; Cotterle, Diego
Abstract: Analysis of multichannel seismic profiles collected on the continental rise off the Sabrina Coast, East Antarctica, has allowed the determination of the acoustic features that are indicative of major evolution steps of the East Antarctic Ice Sheet (EAIS) and highlights the role of meltwater that originated from Totten Glacier in shaping the margin architecture. The arrival of marine-terminating glaciers into the coastal region was recorded by an enhanced sediment input on the continental rise and the nucleation of channel-levees. Downslope sedimentary processes were dominant throughout the Late Cenozoic, testifying to the progressive growth of a highly dynamic, temperate ice sheet on the continent. The last evolutionary step marks the transition to when a full polar glacial regime occurred. The development of a prograding wedge with steeply dipping foresets on the continental shelf and slope exemplifies sedimentation at this time. Other sub-sea-floor observations indicate that downslope fluxes, triggered by glacial meltwater, were still able to deeply erode and deliver sediments to the rise area. This study's findings have led to the identification of expanded and well-preserved sedimentary successions, which we suggest should be considered as priority targets for future International Ocean Discovery Program deep drilling due to the sensitivity of the ice sheet in this area.